1992
DOI: 10.1016/0741-5214(92)90107-j
|View full text |Cite
|
Sign up to set email alerts
|

Elastin content, cross-links, and mRNA in normal and aneurysmal human aorta

Abstract: Although elastin depletion is thought to be an etiologic factor in abdominal aortic aneurysm, little is known about its transcription and posttranslational modification in normal and diseased human aorta. Our objectives were to quantify total elastin and elastin cross-links (desmosine/isodesmosine [DID]) and to determine if elastin mRNA was detectable in the disease-prone infrarenal aorta from patients with abdominal aortic aneurysm and a comparative group with no aneurysmal diseases. After preliminary extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(54 citation statements)
references
References 30 publications
2
51
0
1
Order By: Relevance
“…The pathological hallmark of an aortic aneurysm is considered to be remodeling of the aortic wall, involving fragmentation and a decrease of elastic fibers in the tunica media. 8) In the present case, similar pathological findings to the fragmentation and degeneration of elastic fibers were shown. Although it may be impossible to compare the middle colic artery with the aorta, the pathological findings indicated that fragmented or degenerated elastic fibers may also play an important role in middle colic artery aneurysms.…”
Section: Discussionsupporting
confidence: 70%
“…The pathological hallmark of an aortic aneurysm is considered to be remodeling of the aortic wall, involving fragmentation and a decrease of elastic fibers in the tunica media. 8) In the present case, similar pathological findings to the fragmentation and degeneration of elastic fibers were shown. Although it may be impossible to compare the middle colic artery with the aorta, the pathological findings indicated that fragmented or degenerated elastic fibers may also play an important role in middle colic artery aneurysms.…”
Section: Discussionsupporting
confidence: 70%
“…The elastin concentration in the wall of IRAA aneurysms was about 10 times less than the value in the wall of control IRAA [72]. This was further validated by two other studies that showed that the amount of total elastin in IRAA aneurysm was decreased compared with control [68,74]. These studies also characterized the number of elastin cross-links showing a similar amount to control IRAA, but this could vary depending on the method used.…”
Section: Effects Of Diseasesupporting
confidence: 60%
“…29 Although elective surgical repair is an effective approach to prevent deaths from AAA rupture, there is a conspicuous absence of alternative therapeutic strategies for this disease. 30 Because human aneurysmal tissues are characterized by destructive remodeling of the elastic media and outer aortic wall, recent investigations have emphasized disease mechanisms involving chronic aortic wall inflammation and the progressive degradation of fibrillar matrix proteins.…”
Section: Discussionmentioning
confidence: 99%